The Role of Repeated Exposure to Multimodal Input in Incidental Acquisition of Foreign Language Vocabulary. Issue 4 (15th October 2014) - Bisson, Marie‐Josée; van Heuven, Walter J. B.; Conklin, Kathy; Tunney, Richard J.
<x xml:space="preserve">Abstract</x> Prior research has reported incidental vocabulary acquisition with complete beginners in a foreign language (FL), within 8 exposures to auditory and written FL word forms presented with a picture depicting their meaning. However, important questions remain about whether acquisition occurs with fewer exposures to FL words in a multimodal situation and whether there is a repeated exposure effect. Here we report a study where the number of exposures to FL words in an incidental learning phase varied between 2, 4, 6, and 8 exposures. Following the incidental learning phase, participants completed an explicit learning task where they learned to recognize written translation equivalents of auditory FL word forms, half of which had occurred in the incidental learning phase. The results showed that participants performed better on the words they had previously been exposed to, and that this incidental learning effect occurred from as little as 2 exposures to the multimodal stimuli. In addition, repeated exposure to the stimuli was found to have a larger impact on learning during the first few exposures and decrease thereafter, suggesting that the effects of repeated exposure on vocabulary acquisition are not necessarily constant.